In the Pursuit of Permanence, Is There Only Persistence? Contemporary Graffiti Practices in Toronto - Sabourin, Rachelle (Street Art & Urban Creativity, 2020)
Art as it occurs in the streets is an “other” history. Inherently anti-institutional, it has never fit well within the academy or the museum; basically free, it has consistently had a problematic relationship with the art market; iconoclastic, it is often hard for many to read; and stemming from the countercultural or underground tendencies of youth, it is by and large all too easy for those who “know better” to dismiss it without regard to its content or its intent. Carlo McCormick, “Art in The Streets”